WORKLOADS AND INTERRELATIONSHIPS WITH THE PROGRAM FOR THE HUMANIZATION OF PRENATAL AND CHILDBIRTH CARE - Heitor Silva Biondi; Eliana Cardia de Pinho; Ana Lucia Cardoso Kirchhof; Laurelize Pereira Rocha; Nalú Pereira da Costa Kerber (Universidade Federal do Paraná, 2018)
Objective: to learn the interrelationship between the implementation of care practices proposed in the Pro-gram for the Humanization of Prenatal and Childbirth Care and the workloads in the work process of nurses in obstet-rics centers and maternity hospitals. Method: a qualitative and descriptive study was carried out with 14 nurses at two obstetrics and maternity centers of two hospitals in southern Brazil. Data were gathered from October 2015 to January 2016 through semi-structured interviews, explored with content analysis. Results: two categories emerged: 'Attenuation of workloads', in which biological and psychic workloads stand out, and 'Amplification of workloads', with biological, mechanic and psychic workloads standing out. Conclusion: the way and context in which workloads are processed make them attenuated or amplified when implementing practices proposed in the Program for the Humanization of Prenatal and Childbirth Care.